Ultrasonic Microbubble Cavitation Deliver Gal-3 shRNA to Inhibit Myocardial Fibrosis after Myocardial Infarction - Wenqu Li; Qiaofeng Jin; Li Zhang; Shukun He; Yishu Song; Lingling Xu; Cheng Deng; Lufang Wang; Xiaojuan Qin; Mingxing Xie (MDPI AG, 2023)
Galectin-3 (Gal-3) participates in myocardial fibrosis (MF) in a variety of ways. Inhibiting the expression of Gal-3 can effectively interfere with MF. This study aimed to explore the value of Gal-3 short hairpin RNA (shRNA) transfection mediated by ultrasound-targeted microbubble destruction (UTMD) in anti-myocardial fibrosis and its mechanism. A rat model of myocardial infarction (MI) was established and randomly divided into control and Gal-3 shRNA/cationic microbubbles + ultrasound (Gal-3 shRNA/CMBs + US) groups. Echocardiography measured the left ventricular ejection fraction (LVEF) weekly, and the heart was harvested to analyze fibrosis, Gal-3, and collagen expression. LVEF in the Gal-3 shRNA/CMB + US group was improved compared with the control group. On day 21, the myocardial Gal-3 expression decreased in the Gal-3 shRNA/CMBs + US group. Furthermore, the proportion of the myocardial fibrosis area in the Gal-3 shRNA/CMBs + US group was 6.9 ± 0.41% lower than in the control group. After inhibition of Gal-3, there was a downregulation in collagen production (collagen I and III), and the ratio of Col I/Col III decreased. In conclusion, UTMD-mediated Gal-3 shRNA transfection can effectively silence the expression of Gal-3 in myocardial tissue, reduce myocardial fibrosis, and protect the cardiac ejection function.